A haunting in Hialeah Gardens : a novel - Palma, Raul (Dutton, an imprint of Penguin Random House LLC, 2023)
"Since his wife died, Hugo Contreras's debt from her medical bills has become insurmountable. His world in Miami has shrunk. He shuffles between his efficiency apartment, La Carreta (his favorite place for a cafecito), and a botanica in a strip mall where he works as the resident babaláwo. One day, Hugo's nemesis calls. Alexi Ramirez is a debt collector who has been hounding Hugo for years, and Hugo assumes this call is just more of the same. Except this time Alexi is calling because he needs spiritual help. His house is haunted. Alexi proposes a deal: If Hugo can successfully cleanse his home before Noche Buena, Alexi will forgive Hugo's debt. Hugo reluctantly accepts, but there's one issue: Despite being a babaláwo, he doesn't believe in spirits. Hugo plans to do what he's done with dozens of clients before: use sleight of hand and amateur psychology to convince Alexi the spirits have departed. But when the job turns out to be more than Hugo bargained for, Hugo's old tricks don't work. Memories of his past--his childhood in the Bolivian silver mines and a fraught crossing into the United States as a boy--collide with Alexi's demons in an explosive climax."--